Land Grab and Institutional Legacy of Colonialism: The Case of Sudan - Zambakari, Dr. Christopher (Consilience, 2017)
Over last decade Africa has experienced an unprecedented amounts of land being concessioned, leased or sold to business, corporations or foreign sovereign capital. The land question (who can acquire or have access to land) and the political question (who belongs in the political community) are connected to the citizenship question. These questions are among the most politicized in Africa. This article answers the following questions: Who benefits from the ‘land grabs’? And what can a critical analysis of the ‘land grabs’ tell us about the contemporary politics of development? The first section of this article discusses and provides the intellectual background that informs today’s land rush. The second section discusses the competing actors involved in the land grab, winners and victims. I argue that the majority of victims of land dispossession in the African context are peasants, pastoralists, nomadic, and trans-boundary communities, whose land management system is based on customary land tenure.